Analisis Manajemen Risiko Sistem Informasi Pengelolaaan Data English Proficiency Test (EPT) dan Portal Informasi di UPT Bahasa Universitas Lampung Menggunakan Metode ISO 31000 - Monica Monica; didik Kurniawan; Rizky Prabowo (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2020)
UPT Language University of Lampung (Unila) is one of the Technical Services Unit (UPT) that utilizes information systems to support effectiveness and efficiency in its implementation in the field. The purpose of this study is to analyze the process of information system risk management at the Unila Language UPT using ISO 31000 and produce recommendations for work units about effective control measures and appropriate treatment for the risks faced. Information system risk management at UPT Language Unila is implemented to anticipate the source of risk threats by means of communication and consultation, setting the context (scope), risk assessment, monitoring and review, and handling. The results of this risk management research are, there are 15 possible risks. These risks are classified into 3 risk categories including personnel risk, system and infrastructure risks, and incidental risks. The level of risk is divided into 5 namely, very high risk, high risk, moderate risk, low risk, and very low risk.